DIEP flap for breast reconstruction: Is abdominal fat thickness associated with post-operative complications?. Issue 8 (August 2017) - Modarressi, Ali; Müller, Camillo Theo; Montet, Xavier; Rüegg, Eva Meia; Pittet-Cuénod, Brigitte
Summary: Introduction: Some surgeons consider a high body mass index (BMI) or important abdominal fat excess as contraindications for breast reconstruction with free deep inferior epigastric perforator (DIEP) flap. This study aimed to identify factors associated with post-operative complications by using this type of flap, with an emphasis on BMI and abdominal subcutaneous fat thickness. Methods: A retrospective chart review of 105 consecutive patients who underwent DIEP flap breast reconstruction at our institution was performed to assess post-operative complications. Among other risk factors, we specifically studied the influence of BMI and abdominal wall thickness on complication occurrence. Abdominal wall thickness was measured at 10 different points on the angio-computed tomography scan performed pre-operatively. Results: Median age was 49.8 years (range, 27–69); average BMI was 25.57 kg/m 2 (range, 18.07–41.91). Immediate breast reconstruction was performed for 35% of patients, and five patients (4.7%) underwent bilateral reconstruction. Twenty-six patients (24.8%) presented 29 post-operative complications; 12 concerned abdominal complications (delayed wound healing [n = 6] and seroma [n = 6]) and 17 were related to complications of the reconstructed breast (six minimal necrosis treated conservatively, eight minor necrosis requiring surgical debridement and three total flap loss). The complication rate was not correlated with increased BMI or abdominal wall thickness. The only factor that significantly predicts DIEP flap complications was pre-operative radiotherapy (odds ratio = 4.05; p  = 0.03). Conclusions: No significant correlation was observed between BMI of 25–35 kg/m 2 or abdominal wall thickness and post-operative complications of the donor site or DIEP flap. Therefore, these factors should not be considered as contraindication criteria.